2020
DOI: 10.18700/jnc.200002
|View full text |Cite
|
Sign up to set email alerts
|

Robotically assisted transcranial Doppler with artificial intelligence for assessment of cerebral vasospasm after subarachnoid hemorrhage

Abstract: Background: Transcranial Doppler (TCD) ultrasound is an essential tool for the detection of cerebral vasospasm after subarachnoid hemorrhage (SAH) but is limited by the availability of skilled operators. We examined the clinical feasibility and concordance of a robotically assisted TCD system with artificial intelligence with routine handheld TCD after SAH. Methods: We evaluated TCD velocities in the anterior cerebral artery (ACA) and middle cerebral artery (MCA) of two patients with high-grade SAH and angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…14 This case study found that the MCA mCBFV insonated by NovaGuide were comparable to those measured via an expert; in the evaluation of a patient with angiographically-confirmed vasospasm (concordance correlation coefficient, 0.83; 95% CI, 0.42-0.96; p=0.001). 13 This work is an important compliment to this study, showing equivalence in a pathological population.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…14 This case study found that the MCA mCBFV insonated by NovaGuide were comparable to those measured via an expert; in the evaluation of a patient with angiographically-confirmed vasospasm (concordance correlation coefficient, 0.83; 95% CI, 0.42-0.96; p=0.001). 13 This work is an important compliment to this study, showing equivalence in a pathological population.…”
Section: Discussionsupporting
confidence: 59%
“…4 Recent work has been done to present and evaluate possible solutions to these limitations of TCD, ranging from semi-autonomous insonation of healthy control subjects to fully-autonomous evaluation and indication of angiographic vasospasm after SAH. 12,13 For TCD to become more widely utilized, the limitations of both operation and analysis must be addressed. Here we sought to evaluate the performance of a novel, fully autonomous robotic TCD (rTCD) system, NovaGuide (NovaSignal Corp., Los Angeles, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when we applied the mean CBFv threshold for mild vasospasm to the maximum CBFv (Max CBFv ≥ 120 cm/s) from the NovaGuide data we obtained a performance comparable to previous publications. A meta-analysis of 26 studies comparing TCD against angiography found that utilizing the criteria of mean CBFv > 120 cm/s TCD had a sensitivity of 67% (48–87%), specificity of 99% (99–100%), positive predictive value of 97% (95–98%), negative predictive value of 78% (65–91%), positive likelihood ratio of 17 (5–56) ,and negative likelihood ratio of 0.4 (0.2–0.7) 14 . Our metrics of sensitivity (83%), negative predictive value (90%), and positive likelihood ratio (8.75) are contained within these reported ranges.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures the acquired velocities are representative of the current flow dynamics of the MCA. While the MCAs are the only vessel the robotic TCD will autonomously locate and measure, the internal carotid artery terminus anterior cerebral arteries, and posterior cerebral arteries, can be measured manually 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The incidences of morbidity and mortality due to vasospasm are both around 20% [ 8 , 9 ]. Vasospasm can be diagnosed by transcranial Doppler (TCD) ultrasonography and transcranial color-coded Doppler (TCCD) ultrasonography, albeit with limited accuracy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%